On the L2-pointwise Regularity of Functions in Critical Besov Spaces - Moussa, Mohamed (Revista Matemática Complutense, 2004)
We show that the functions in L2(Rn) given by the sum of infinitely sparse wavelet expansions are regular, i.e. belong to C1L2 (x0), for all x0 2 Rn which is outside a set of vanishing Hausdorff dimension.